Long-term impact of grazing and tillage on soil quality in the semi-arid Chaco (Argentina) - Banegas, Natalia Romina; Maza, Marianela; Viruel, Emilce; Nasca, Jose Andres; Canteros, Francisco H.; Corbella, Roberto; Dos Santos, Daniel Andrés (Sociedad Española de la Ciencia del Suelo, 2019)
Deforestation of Chacoan native forests and reorientation of land use are transforming the region into agricultural use. The main purpose of this work was to evaluate the impact of different land uses on soil quality in the semi-arid Chaco (Argentina). We assessed the behaviour of soil parameters over four years of experimental conditions: 1) Exclosure pasture (EP) used as reference level, 2) Grazed pasture (GP), 3) Grazed pasture transformed to agriculture with Zero tillage (ZT) and 4) Grazed pasture transformed to agriculture under Conventional tillage (CT). Soil organic carbon, particulate and heavy organic carbon (C), total nitrogen (N), C:N ratio, pH, electric conductivity and soil respiration were measured. Soil samples were taken yearly at 0-5, 5-20 and 20-40 cm of soil depth. Differences among treatments across time were assessed by Analysis of Covariance (ANCOVA) with time (years) as covariate factor, treatments as group factor and individual scores from Principal Component Analysis (PCA) as responses. Correlated changes in the soil characteristics were detected, especially at the top soil layer. Both carbon and nitrogen contents increased in both GP and ZT systems. An opposite trend was found for CT, which also had a negative impact on salinity. Both land use change and management practices in the Chaco region represent the main human activities that modify the landscape; thus, they should be analysed by recognizing heterogeneity on farming practices and identifying their impacts on a specific site. The results of this work reinforce the utility of soil organic carbon as a single parameter for monitoring land management systems, especially for monitoring large region like Chaco that are subject to continuous transformation processes.